PERSEPSI PELAKU UKM TERHADAP LAPORAN KEUANGAN BERDASARKAN STANDAR AKUNTANSI KEUANGAN ENTITAS TANPA AKUNTABILITAS PUBLIK (SAK ETAP) - Nurul Hidayah; Nur Sayidatul Muntiah (Jurnal Akuntansi Indonesia, 2019)
This study aims to determine the perceptions of batik SMEs “Pring Sedapur” on the preparation of financial reports based on SAK ETAP in Sidomukti Village, Plaosan District, Magetan Regency. This study used a survey method with a quantitative approach that was conducted on 3 respondents. The technique of collecting data uses structured interviews, interviews, and document studies. and data analysis techniques use descriptive analysis techniques.The results showed that the factors of age, education and the length of time to open a business / experience did not indicate a difference of opinion about their perceptions of the application of accounting. SMEs have made accounting records even though they are still very simple. They have not made journals, ledgers and prepared financial reports in accordance with SAK ETAP, because of limited knowledge and information on how to apply accounting in accordance with SAK ETAP.